2015
DOI: 10.12989/sss.2015.15.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Application of model reduction technique and structural subsection technique on optimal sensor placement of truss structures

Abstract: Abstract. An optimal sensor placement (OSP) method based on structural subsection technique (SST) and model reduction technique was proposed for modal identification of truss structures, which was conducted using genetic algorithm (GA). The constraints of GA variables were determined by SST in advance. Subsequently, according to model reduction technique, the optimal group of master degrees of freedom and the optimal objective function value were obtained using GA in a case of the given number of sensors. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The greater the redundancy in the information collected by the two sensors, the more similar their corresponding information matrices are. To quantify that, Euclidean distance is introduced in this study to evaluate the redundancy level of any two measurement points as shown in equation (17):…”
Section: Redundancy Reduction Based On Dc-ei Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater the redundancy in the information collected by the two sensors, the more similar their corresponding information matrices are. To quantify that, Euclidean distance is introduced in this study to evaluate the redundancy level of any two measurement points as shown in equation (17):…”
Section: Redundancy Reduction Based On Dc-ei Methodsmentioning
confidence: 99%
“…The main idea behind it is to achieve an unbiased estimate of modal coordinates by maximizing the determinant of the Fisher information matrix (FIM). In addition to the classical approaches, novel evolutionary optimization algorithms, such as the genetic algorithm [13][14][15][16][17], monkey algorithm [18,19], firefly algorithm [20,21], and particle swarm optimization algorithm [22], were also utilized to address some of the complex problems arising during the OSP process. All of these evolutionary algorithms have shown promising results in addressing the OSP problem for different large-scale structures, such as suspension bridges [21], dams [23], and high-rise buildings [24].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with those devoted to modal identification, the OSP methods aiming at damage detection are far from maturing . In this context, OSP methods based on modal and residual sensitivity have been proposed, and model reduction techniques have been introduced to facilitate solution to the OSP problem . Advanced computing techniques, such as neural network, genetic, simulated annealing, and monkey algorithms have been applied for OSP .…”
Section: Introductionmentioning
confidence: 99%